A study on variations in occlusion among Filipino twins - Balobalo, Ma. Iselle
Early studies has led the orthodontic specialty in general to conclude that genes are fundamental in causing malocclusion. One classic way of studying the etiology of malocclusion in relation to genetics and/or environment is by studying twins, by comparing monozygotic or identical twins to dizygotic or fraternal twins. 12 sets of Filipino twins were taken as samples, 2 fraternal, 2 identified identical twins, and 8 others of undetermined zygosity. Pictures and dental casts were taken and dental characters were measured and observed. Dental characters include overjet, overbite, arch perimeter, intercanine diameter, ineterfirstmolar dimension, mesio-distal tooth sizes, molar relationship, and presence of rotation, supraeruption and crossbite. The results were analyzed by using simple statistics and Anova testing. It revealed that overjet, the tooth sizes of 16, 15, 12, and 11 has significant statistical findings thus are deemed to be heritable traits. Individual tooth displacement characteristics and facial profile were also found to be under genetic influences. The rest of the variables are thereby attributed to be under environmental influences.